Satellite remote sensing for ice sheet research - Thomas, R. H; United States. National Aeronautics and Space Administration. Scientific and Technical Information Branch (Washington, D.C. : National Aeronautics and Space Administration, Scientific and Technical Information Branch, 1985)
Mode of access: Internet.